Σ-Approximately Contractible Banach Algebras. (9th August 2012) - Momeni, M.; Yazdanpanah, T.; Mardanbeigi, M. R.
Abstract : We investigate σ -approximate contractibility and σ -approximate amenability of Banach algebras, which are extensions of usual notions of contractibility and amenability, respectively, where σ is a dense range or an idempotent bounded endomorphism of the corresponding Banach algebra.